1993
DOI: 10.1084/jem.177.6.1613
|View full text |Cite
|
Sign up to set email alerts
|

Persistent calcium elevation correlates with the induction of surface immunoglobulin-mediated B cell DNA synthesis.

Abstract: SummarySurface immunoglobulin (slg)-mediated stimulation of B lymphocytes induces a tyrosine kinase-dependent sequence of events leading to rapid and large elevations in intracellular ionized calcium ([Ca2+]i). These early biochemical events do not necessarily lead to proliferation of B cells, however, and conversely, the absence of or inhibition of these events does not necessarily prevent cellular proliferation. We now show by digital image analysis of single B cells that conditions which lead to B cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Phosphorylation of CD79a Tyr182 by LPS, however, was slower than that following induction by anti–δ mAb/dex or soluble/monomeric anti–Igμ antibody. Also, like anti–δ mAb/dex, which induced a continuous increase of the free cytosolic Ca 2+ ion level, as a hallmark of persistent BCR signaling (200), LPS, but not lipid A or CD154, induced Ca 2+ elevation, which was detectable within minutes of stimulation and further increased after a longer period of stimulation (23). Furthermore, B cells deficient in known BCR signaling elements, such as CD19, Btk, Blnk, Lyn or Vav, displayed greatly reduced responses to LPS (201-205).…”
Section: Tlrs Trigger T Cell-independent But Limited Csrmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation of CD79a Tyr182 by LPS, however, was slower than that following induction by anti–δ mAb/dex or soluble/monomeric anti–Igμ antibody. Also, like anti–δ mAb/dex, which induced a continuous increase of the free cytosolic Ca 2+ ion level, as a hallmark of persistent BCR signaling (200), LPS, but not lipid A or CD154, induced Ca 2+ elevation, which was detectable within minutes of stimulation and further increased after a longer period of stimulation (23). Furthermore, B cells deficient in known BCR signaling elements, such as CD19, Btk, Blnk, Lyn or Vav, displayed greatly reduced responses to LPS (201-205).…”
Section: Tlrs Trigger T Cell-independent But Limited Csrmentioning
confidence: 99%
“…PI(3)K generates phosphatidylinositol (3,4,5) triphosphate on the inner leaflet of the plasma membrane, where signaling molecules such as phospholipase Cγ2 (PLCγ2) and AKT are recruited upon binding of phosphatidylinositol (3,4,5) triphosphate through their pleckstrin homology (PH) domain. Membrane-localized PLCγ2 cleaves phosphatidylinositol lipids to generate diacylglycerol (DAG), which activates protein kinase C-β (PKC-β) (224), and inositol triphosphate (IP3), which results in elevation of intracellular Ca 2+ levels (200, 225, 226). PKC-β activates the CARMA1 signalosome complex composed of CARMA1, BCL10 and MALT1, resulting in TRAF6 ubiquitination and subsequent TAK1-mediated IKK phosphorylation for canonical NF-κB activation and/or TAK1-triggered MAPK cascades for JNK, ERK and/or p38 activation (227).…”
Section: Tlr and Bcr Signaling Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for DNA synthesis to occur and for B cells to proliferate upon BCR crosslinking, there must be a small, but sustained increase in cytoplasmic free calcium [14]. Furthermore, B cell stimulation via BCR crosslinking can be successfully mimicked using calcium ionophores (such as ionomycin) to increase cytoplasmic free calcium, in combination with phorbol esters (such as PMA) to activate PKC [15].…”
Section: The Role Of Plcr In Bcr Signalingmentioning
confidence: 99%
“…Previous studies have demonstrated that multivalent cross-linking of membrane IgD and specific costimulation with IL-4 and IL-5 serve as such a model for TI-2 responses (46,47). Therefore, we incubated purified splenic B cells from wt C57BL/6 mice with a dextran-coupled anti-IgD mAb (␣␦-dex), IL4, IL-5, and IGF-1, alone or in combination (Fig.…”
Section: Igf-1 Promotes Ig Production In An In Vitro Model Of Ti-2 Rementioning
confidence: 99%